PERTANGGUNGJAWABAN PIDANA PELAKU KEKERASAN SEKSIAL PADA ANAK DI LINGKUNGAN PONDOK PESANTREN: Studi Kasus Putusan Pengadilan No. 989/Pid.Sus/2021/PN Bdg - Asti Virandhany (2022)
Sexual violence against children is currently the most discussed topic because it occurs a lot in Indonesia. KPAI Bank data shows that in 2020 there were 419 cases of sexual violence against children, including non-rape and harassment. The Commission Against Violence Against Women even mentions the critical status of sexual violence due to the weak handling efforts by the state. Including law enforcement against perpetrators. Sexual violence against children itself also occurs in the community, both in the family environment and even in the educational environment. In 2021 there were cases of sexual violence against children in the educational environment of Islamic boarding schools involving 13 victims who were underage. Islamic Boarding School which should be a place of education in order to form human resources with akhlakul karimah actually become a place for indecent acts to occur. This study examines the factors that cause sexual violence against children in Islamic boarding schools and the criminal responsibility of perpetrators of sexual violence against children in Islamic boarding schools. In this study, the author uses a normative juridical method using a statutory approach (Statute Approach) and a case approach (Case Approach). The method of collecting data that the author uses is library research. The results of this study indicate that child protection is very important because children's development is greatly affected by what they experience. With the Law on Child Protection, perpetrators of sexual violence against children in Islamic boarding schools can be prosecuted according to applicable law. Keywords: sexual violence, children, Islamic Boarding School